Depression Screening Implementation in a Primary Care Clinic - Williams, Schuyler (My University, 2020)
Depression is a common disorder that impacts one’s quality of life. It can cause significant medical, social, and financial complications to an individual and affect others close to the person suffering from it. Depression is often underrecognized and underdiagnosed in the primary care setting, which can lead to inadequate treatment. Depression screening has been proven to be effective in detecting symptoms during an office visit. The purpose of this quality improvement project was to implement a Patient Health Questionnaire (PHQ-9) depression screening process in a rural primary care clinic. Based on the total score of the PHQ-9 screening test or if question number 9 is one or greater, the Columbia-Suicide Severity Rating Scale (C-SSRS) questionnaire was administered by the provider to further assess suicidal risk. The goal was for 100% administration of the PHQ-9 screening tool to all non-acute patient visits. Biweekly PDSA reviews were conducted, to evaluate the clinic’s progress and modifications were incorporated as needed. During the 13-week project period, 312 patients completed the PHQ-9 and 13 scored high enough to be considered mild depression, and no patients met screening criteria for the C-SSRS questionnaire. The goal of 100% administration of the PHQ-9 questionnaire was achieved during the last month’s implementation at week ten and week twelve. The PHQ-9 screening tool is a cost-effective way to detect symptoms sooner and allow the provider to help reduce the patient’s functional impairments, reduce the risk of suicide, and increase the likelihood of adhering with medical treatment.
Keywords: Depression, Patient Health Questionnaire, PHQ-9 Depression Screening, Primary Care, and Implementing Depression Screening